Botanical Shakespeare : an illustrated compendium of all the flowers, fruits, herbs, trees, seeds, and grasses cited by the world's greatest playwright /: an illustrated compendium of all the flowers, fruits, herbs, trees, seeds, and grasses cited by the world's greatest playwright. (2017) - Quealy, Gerit
No abstract available